PERAN MILITER DALAM POLITIK LUAR NEGERI AMERIKA SERIKAT - Yumitro, Gonda (Jurnal Bestari, 2008)
America, which is known to be concerned about democracy and human right issues, seems like having big charity to guarantee the human life, welfare and safe in the entire world. And it becomes the nation's official brand. Hut in fact most of American foreign policies tend to have military characteristics, such as Iraq, Afghanistan, Vietnam, and a many other cases. in December 2007, American soldiers were stationed at more than 820 installations in at least 39 countries. Internally', the armed forces formation is very strong and supported by big financial budget. American armed forces lay on the top list among the countries because of its military expenses and budget. That is the why American military can intluence American foreign policy. American armed forces in American foreign policy decision making system covered big opportunity, regardless of the strategic position of the actors. Consequently, military could gain their pragmatic interest to get budget supporting. This military policy was also powered by the characteristics of the president who would lead the rule.